Results from a randomized controlled pilot trial of a home-visiting intervention to reduce child maltreatment - Joakim Finne; Anne Grete Tøge; Kjersti Stabell Wiggen; Maria Ekre; Ira Malmberg-Heimonen; Maiken Pontoppidan; Jacinthe Dion; Truls Tømmerås; Eirin Pedersen (Pilot and Feasibility Studies)
Abstract Background Child maltreatment has severe and lasting consequences, and evidence-based interventions are essential for its prevention. However, few randomized controlled trials (RCTs) have been conducted within child welfare settings in Norway. Pilot trials play an important part in assessing the acceptability and feasibility of such interventions prior to full scale evaluations. This study evaluated the acceptability and feasibility of conducting a full-scale RCT of the Family Partner home-visiting intervention, designed to reduce the risk of child maltreatment. Methods Families from three child welfare offices in Norway with at least one child under the age of 12 were invited to participate in this pilot trial. A two-arm randomized design was used, with participants allocated in a 1:1 ratio to either the intervention or control group (n = 45). The intervention group received the home-visiting Family Partner intervention, while the control group received treatment as usual. A qualitative process evaluation was conducted alongside the trial, comprising 29 interviews with Family Partners, caseworkers, participating families, and other stakeholders. Statistical and qualitative analyses evaluated participant acceptability, adherence, and retention. Results Qualitative findings indicate a high level of acceptability for the Family Partner intervention across all stakeholder groups. Adherence was strong, with no participants withdrawing consent and only two opting out of subsequent surveys. However, participant retention declined over time, with survey response rates dropping at each time point and only 42% completing the final assessment. Conclusions This pilot trial provides preliminary evidence supporting the acceptability of the Family Partner intervention within child welfare services and highlights important considerations regarding the feasibility of conducting RCTs in this setting. Trial registration ClinicalTrials.gov identifier NCT04957394.